Yudi man mga osipon para ki Nunuy asin ki Nini - Arejola, Carlos A.; Billanes, Lorna A.; Abrenica, Boyet (Manila National Commission for Culture and the Arts, 2009)
A collection of short stories for children.
Children's literature.
In Bikol
Keywords: Short stories, Bikol -- Juvenile literature; Bikol literature; Children's literature, Philippine; Philippine fiction (Bikol) -- Juvenile literature